AI powered asthma prediction towards treatment formulation : An android app approach - Murad, Saydul Akbar; Adhikary, Apurba; Muzahid, Abu Jafar Md; Sarker, Md. Murad Hossain; Khan, Md. Ashikur Rahman; Hossain, Md. Bipul; Bairagi, Anupam Kumar; Masud, Mehedi; Kowsher, Md. (Tech Science Press, 2022)
Asthma is a disease which attacks the lungs and that affects people of all ages. Asthma prediction is crucial since many individuals already have asthma and increasing asthma patients is continuous. Machine learning (ML) has been demonstrated to help individuals make judgments and predictions based on vast amounts of data. Because Android applications are widely available, it will be highly beneficial to individuals if they can receive therapy through a simple app. In this study, the machine learning approach is utilized to determine whether or not a person is affected by asthma. Besides, an android application is being cre-ated to give therapy based on machine learning predictions. To collect data, we enlisted the help of 4,500 people. We collect information on 23 asthma-related characteristics. We utilized eight robust machine learning algorithms to analyze this dataset. We found that the Decision tree classifier had the best performance, out of the eight algorithms, with an accuracy of 87%. TensorFlow is utilized to integrate machine learning with an Android application. We accomplished asthma therapy using an Android application developed in Java and running on the Android Studio platform.